Book Review: Lawyers and Savages; Ancient History and Legal Realism in the Making of Legal Anthropology - Gloria Lee (Oñati Socio-Legal Series)
Book review of Kaius Tuori. Lawyers and Savages; Ancient History and Legal Realism in the Making of Legal Anthropology. Oxon; New York: Routledge 2015, pp. 224, ISBN (Pb) 9781138685949 £34.99, ISBN (Hb) 9780415737012 £95.00, ISBN (eBook) 9781317816201 £24,49.